The EdibleDemocracy : Fact or Just Politic Discourse - สิงห์มาตร สนุก; เคณาภูมิ ผู้ช่วยศาสตราจารย์ดร.สัญญา (Journal for Developing the Social and Community, 2015)
Democracy is the sovereignty of the people, by the people and for the people. Democracy in Thailand is just the process of one governing only; it’s not the majority of people. Making a public policy just for acquiring voting is not a complete approach of public policy making. Thus, the approach for public policy making of political parties should be based on 2 concepts; (1) Policy for reserve a voice, And(2) Policies for developing countries completely.